Advanced heat resistant steels for power generation : conference proceedings 27-29 April 1998 San Sebastian, Spain - Viswanathan, Ramaswamy; Nutting, Jack, 1924- (IOM Communications, 1999)
Organised by the Electric Power Institute, this conference attracted 135 delegates from 17 countries. The proceeding volume represents a state-of-the-art overview of the latest developments in 9-12 Cr steels and their applications in power generation equipment.
Keywords: Steel, Heat resistant -- Congresses.; Electric power production -- Congresses.; elektronické knihy; electronic books